(untitled) (Research, Society and Development, 2024)
This investigation aims to identify one of the main production losses in a toothpaste production line to optimize the production process and thereby reduce the amount of industrial waste generated. The study used analytical tools like brainstorming, 5W2H, and Time and Motion Observation to identify the main problems. The analysis revealed that the line lost toothpaste tubes at the end of each production order due to the lack of a standard procedure and insufficient production control. To identify causes, we used methods like the Ishikawa Diagram and the “5 Whys”, which identified overproduction as the main contributing factor to material disposal. The action plan followed the PDCA cycle, established standardized procedures, and created a counting and communication system between the equipment. Implementing these improvements, there was a 78% reduction in the amount of discarded material and a 51-minute increase in the operator’s productive capacity. Project management was facilitated using the Gantt Chart, which helped identify and overcome bottlenecks throughout the study, despite a slight extension in the estimated delivery time. This paper demonstrates how using methodologies and concepts from Production Engineering, such as Process Analysis, Quality Management, Project Management, Production Control, and Sustainability, can lead to notable enhancements in the efficiency and sustainability of industrial operations.